"Não existe babaçu livre em terra presa": estratégia, autonomia e resistência dos babaçuais - Brito, Kathiane Santana (2019)
This paper analyzes the trajectory of MIQCB, especially in Maranhão, its organizational forms, its struggles to secure rights to coconut breakers and its resistance to the devastation of the Babaçu Ecological Region. The named Babassu Ecological Region, an area of 27 million hectares that extends from the Parnaíba Valley to Tocantins-Araguaia, covering the states of Maranhão, Piauí, Pará and Tocantins, place of extensive babassus Coconut Babassu, where women groups that named themselves babassu coconut breakers, excercise their activity of collecting Coconut Babassu and earning income for their families, facing difficulties caused by agribusiness, which destroys the Babassu palm, endangering your own identity of “Coconut babaçu breaker". In the face of these conflicts, the breakers organized the MIQCB, as the form organizative of representing your social, political, economic and cultural interests, forward their struggles for free access to territory and resources, valorization of the coconut chain. babassu, training through contextualized education, access to public policies, preservation of babassu palms and the autonomy of the production process. For the methodology of this research were used readings, participation in meetings, public hearing, speech transcripts, interviews, studies of social cartography, visits to the headquarters of MIQCB in São Luís, the use of internet with access to websites of Organizational Forms, information that collaborated in the construction of my object of study. Therefore, debating and making visible the actions of coconut breakers in the face of the rights violations they have been suffering is essential to strengthen them.